2010
DOI: 10.1590/s0044-59672010000100006
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de Hymenaea courbaril L. var. stilbocarpa (Hayne) Lee et Lang. e Enterolobium contortisiliquum (Vell.) Morong (Leguminosae) sob diferentes níveis de sombreamento

Abstract: Hymenaea courbaril L. var. stilbocarpa (Hayne) Lee et Lang. é uma espécie clímax tolerante a sombra, ao passo que Enterolobium contortisiliquum (Vell.) Morong. é uma espécie pioneira. O desenvolvimento destas espécies pode refletir a habilidade de adaptação aos diferentes fatores ambientais (luz, água e temperatura) no local em que estão crescendo. O suprimento inadequado de um desses fatores pode reduzir o vigor da planta e limitar seu desenvolvimento. O presente trabalho teve como objetivo avaliar os efeitos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
1
21

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 24 publications
6
26
1
21
Order By: Relevance
“…In general, plants grown in shaded conditions show a low ratio of chlorophyll a/b due to slow degradation of chlorophyll b (Engel & Poggiani, 1991). According to Lima et al (2010), E. contortisiliquum plants grown in shade had high values of total chlorophyll, indicating a high investment in light capture. The high total chlorophyll index in plants grown in the shade results from continuous synthesis of chlorophyll molecules; however, in sun leaves, the chlorophyll degradation process occurs faster, thus decreasing the leaf chlorophyll content (Engel & Poggiani, 1991;Kramer & Kozlowski, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, plants grown in shaded conditions show a low ratio of chlorophyll a/b due to slow degradation of chlorophyll b (Engel & Poggiani, 1991). According to Lima et al (2010), E. contortisiliquum plants grown in shade had high values of total chlorophyll, indicating a high investment in light capture. The high total chlorophyll index in plants grown in the shade results from continuous synthesis of chlorophyll molecules; however, in sun leaves, the chlorophyll degradation process occurs faster, thus decreasing the leaf chlorophyll content (Engel & Poggiani, 1991;Kramer & Kozlowski, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…According to Scalon et al (2006), E. contortisiliquum plants under full sun showed higher values of root and total dry mass and height than shaded plants. On the other hand, Lima et al (2010) and Melo et al (2008) found that shaded E. contortisiliquum plants showed higher height, root length, and total dry mass than those grown in sun. These contrasting responses could be a result of the ability of E. contortisiliquum to adjust to varying environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the presence a floured pulp that involves its embryo (BUSATTO et al, 2013), the species is an important food resource for fauna, that disperse its seeds. Such fact reinforces the importance of preserving and performing plantations of the species in degraded areas intended for the recomposition of the arboreal vegetation (LIMA; ZANELLA; CASTRO, 2010).…”
Section: Introductionmentioning
confidence: 68%
“…A área foliar maior sob sombra, certamente, ocorreu devido à necessidade de a planta ampliar a superfície fotossintetizante para maximizar a absorção luminosa. Efeito positivo do sombreamento, em comparação ao pleno sol, sob a altura de mudas foi verificado em Hymenaea courbaril l. (lIMA et al , 2010); Schizolobium amazonicum Huber ex Ducke (RoSA et al, 2009); Brosimum rubescens Taub. (MARIMoN et al, 2008).…”
Section: Resultsunclassified